2019
DOI: 10.1126/sciadv.aau8763
|View full text |Cite
|
Sign up to set email alerts
|

Quantum plasmonic control of trions in a picocavity with monolayer WS 2

Abstract: Monitoring and controlling the neutral and charged excitons (trions) in two-dimensional (2D) materials are essential for the development of high-performance devices. However, nanoscale control is challenging because of diffraction-limited spatial resolution of conventional far-field techniques. Here, we extend the classical tip-enhanced photoluminescence based on tip-substrate nanocavity to quantum regime and demonstrate controlled nano-optical imaging, namely, tip-enhanced quantum plasmonics. In addition to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Similarly, the TEPL linewidth (FWHM) decreases at the wrinkle from ≈52 to ≈48 meV due to the symmetrically modified spectral shape, as shown in Figure 3b. The asymmetric nature of the TEPL spectrum at the crystal face is attributed to the trion and biexciton shoulders [7,41] and asymmetric phonon sidebands caused by the strong exciton-phonon coupling. [23] Therefore, from the modified spectral shape and the linewidth map, we believe that the exciton PL response is more significantly influenced by the induced tensile strain at the wrinkle compared to the PL responses of trions and biexcitons.…”
Section: Spatio-spectroscopic Investigations Of Excitonic Properties Of Nanoscale Wrinklesmentioning
confidence: 97%
“…Similarly, the TEPL linewidth (FWHM) decreases at the wrinkle from ≈52 to ≈48 meV due to the symmetrically modified spectral shape, as shown in Figure 3b. The asymmetric nature of the TEPL spectrum at the crystal face is attributed to the trion and biexciton shoulders [7,41] and asymmetric phonon sidebands caused by the strong exciton-phonon coupling. [23] Therefore, from the modified spectral shape and the linewidth map, we believe that the exciton PL response is more significantly influenced by the induced tensile strain at the wrinkle compared to the PL responses of trions and biexcitons.…”
Section: Spatio-spectroscopic Investigations Of Excitonic Properties Of Nanoscale Wrinklesmentioning
confidence: 97%
“…Recently, He et al demonstrated the local control of radiative emission of neutral excitons and trions in WS 2 monolayer through precision gap control between Ag tip and Au substrate [149]. Figure 16A shows a schematic illustration of the experimental setup.…”
Section: Applications To 2d Materialsmentioning
confidence: 99%
“…Figure 3 b shows the spectral evolution of a -TEPL response with respect to the distance between Au tip and the crystal on Au film. a -TEPL gradually increases from d = 10 nm to 5 nm owing to the localized antenna effect of Au tip, and is further enhanced at d < 5 nm by the strong interaction between tip-dipole and image-dipole, which shows a similar behavior to the normal TEPL response 24 , 25 . We then obtain a -TEPL image of a WSe 2 monolayer with the same Au tip to quantify the spatial resolution, which is needed to estimate TEPL enhancement factor.…”
Section: Resultsmentioning
confidence: 83%